2018
DOI: 10.1080/01448765.2018.1498389
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nitrogen availability in pot grown crops with organic fertilization

Abstract: Pot grown herbs are often cultivated as certified organic products, and there is an increasing demand for organically certified ornamental plants. Supplying the required nutrients using organic fertilizers is a challenge with respect to matching the mineralization and thus the availability of dissolved nutrients in the growing medium with plant demand. In experiments, sweet basil and Pelargonium × hortorum were cultivated using two different organic fertilizer strategies and controlled-release mineral nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
1
10
0
3
Order By: Relevance
“…Under these conditions, the development of radicle, hypocotyl, and cotyledons was strongly inhibited ( Figure 5B). Similar adverse effects of ammonical N forms on germination and seedling development were reported for several plant species (Bremner and Krogmeier, 1989;Ells et al, 1991;Britto and Kronzucker, 2002;Qi et al, 2012;Bergstrand et al, 2018).…”
Section: Discussion N Dynamic In the Substrate After Organic N Fertilsupporting
confidence: 80%
See 2 more Smart Citations
“…Under these conditions, the development of radicle, hypocotyl, and cotyledons was strongly inhibited ( Figure 5B). Similar adverse effects of ammonical N forms on germination and seedling development were reported for several plant species (Bremner and Krogmeier, 1989;Ells et al, 1991;Britto and Kronzucker, 2002;Qi et al, 2012;Bergstrand et al, 2018).…”
Section: Discussion N Dynamic In the Substrate After Organic N Fertilsupporting
confidence: 80%
“…A study on wheat has shown that the seed germination of this cereal species is unaffected at NH 3 concentration below 0.3 ppm, but completely inhibited at 0.8 ppm (Pairintra, 1973). For pot grown basil, a poor germination and weak plant growth was observed when the NH 4 + -N concentration was between 100-130 mg (L substrate) -1 in the first 3 weeks after sowing (Bergstrand et al, 2018). In contrast, Frerichs et al (2017) reported that the germination process of basil was not adversely affected by NH 4 + -N levels at about 200 mg (L substrate) -1 .…”
Section: Discussion N Dynamic In the Substrate After Organic N Fertilmentioning
confidence: 99%
See 1 more Smart Citation
“…in order to allow the nitrification process starting, thus preventing the initial ammonium accumulation and enhancing the total nitrate amount released to plants over the entire crop cycle. However, the low nitrification rate recorded by Bergstrand et al [38] upon poultry manure application may have been caused by the peat-based substrate, which is sometimes characterized by a faster conversion from organic to ammonium form, compared to the subsequent nitrification [39]. In this respect, the sandy-loam soil used in our investigation has a higher air permeability than the peat substrate, thus increasing the nitrification rate [40].…”
Section: Discussionmentioning
confidence: 87%
“…A study regarding the mineralisation of N for container grown crops has previously been published by the authors of this study (Bergstrand et al 2019). In the study reported here, the focus has been expanded to all essential nutrients and tomato was used as the model crop.…”
Section: Introductionmentioning
confidence: 99%